2012
DOI: 10.1111/j.1582-4934.2011.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypobaric hypoxia applicability in myocardial infarction prevention and recovery

Abstract: Intermittent hypobaric hypoxia (IHH) has been the focus of important research in cardioprotection, and it has been associated with several mechanisms. Intermittent hypobaric hypoxia inhibits prolyl hydroxylases (PHD) activity, increasing the stabilization of hypoxia-inducible factor-1 (HIF-1) and activating crucial adaptative genes. It has been hence suggested that IHH might be a simple intervention, which may offer a thoughtful benefits to patients with acute myocardial infarction and no complications. Nevert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…Animal experiments have shown that antioxidants could be beneficial in OSA confirming the role of oxidative stress in this sleep-related disorder [18]. On the other hand, intermittent hypoxia has also been suggested to have some protective effects against some cardiovascular complications [19] and may even have some therapeutic benefit in patients with COPD as it may improve ventilation [20]. Given the complicated hormonal and physiological milieu of pregnancy, which includes a higher inflammatory state, it is unclear how OSA would impact oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have shown that antioxidants could be beneficial in OSA confirming the role of oxidative stress in this sleep-related disorder [18]. On the other hand, intermittent hypoxia has also been suggested to have some protective effects against some cardiovascular complications [19] and may even have some therapeutic benefit in patients with COPD as it may improve ventilation [20]. Given the complicated hormonal and physiological milieu of pregnancy, which includes a higher inflammatory state, it is unclear how OSA would impact oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that intermittent hypobaric hypoxia may produce harmful biochemical changes, including decreased antioxidant capacity and increased lipid peroxidation, which may lead to suppression of vascular endothelial function and impairment of vascular hemodynamics. 67…”
Section: Iht In Hypobaric Chambersmentioning
confidence: 99%
“…Ainsi, l'utilisation de l'hypoxie intermittente par inhalation de mélanges hypoxiques se développe sans que les limites, bénéfices et dangers de cette technique ne soient encore clairement établis [15,16].…”
Section: Effets Bénéfiques De L'altitude Chez Les Patients Atteints Dunclassified